DESKRIPSI KEMAMPUAN PEMECAHAN MASALAH DAN MINAT BELAJAR MAHASISWA SETELAH MENERAPKAN METODE PROBLEM BASED LEARNING DALAM PEMBELAJARAN AGAMA ISLAM - Salahudin, Salahudin; Subhan, Subhan (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Mulawarman, 2021)
This study aims to describe the problem solving ability and interest in student learning after the PBL learning model is applied. This type of research is descriptive research. The subjects of this study were second semester students, totaling 90 students. The instrument used in measuring students' problem-solving abilities was using essay test questions and to measure interest in learning was a questionnaire. To analyze the data using descriptive statistics. The results showed that the problem-solving ability in the very high category was 18 students, for the high category there were 68 students and the sufficient category was 4 people. For interest in learning, the very high category was 59 students, for the high category there were 31 students. Thus, the application of PBL in PAI learning is able to provide good results on problem solving abilities and student interest in learning.